Предмет: Математика,
автор: cett2
преобразовать в многочлен (а+3в квадрате =(а+2)(а-2) срочно надо зарание спасибо
Ответы
Автор ответа:
0
a+3^2*(a+2)(a-2)=(9*(a-2))*(a+2)+a
Автор ответа:
0
1)a(в квадрате) + 9 = а(в квадрате) - 4
2)а(в квадрате) - а(в квадрате) + 9 + 4 = 0
2)а(в квадрате) - а(в квадрате) + 9 + 4 = 0
Похожие вопросы
Предмет: Геометрия,
автор: Misha13062007
Предмет: МХК,
автор: nadjicovamirana95
Предмет: Алгебра,
автор: leshandr08
Предмет: Математика,
автор: Аврорита555
Предмет: Физика,
автор: sh322223hs